THE DETERMINANT OF TAX EVASION DURING PANDEMIC COVID 19 IN JAKARTA - IBRAHIM, IDA; Syahrial, Irzan; Arifin, Zainal (The Global Academia Publisher, 2024)
The present research seeks to empirically examine whether tax justice, technology, tax information, and taxpayer knowledge have an impact on tax evasion during the COVID-19 pandemic. Utilizing primary data, this research sample consists of Jakarta taxpayers who have tax identification numbers. This research method combines stratified random sampling with the formulas of Isaac and Michael. 150 participants constituted the sample size for this investigation. The multiple regression procedure was used to analyze the data. The method of analysis utilized by the SPSS 25 statistical program. The findings indicate that tax justice has an important impact on tax evasion. The lower the tax justice, it is seen as reasonable behavior. To reduce the rate of tax evasion, it should be implemented properly and correctly. Technology and tax information have a substantial influence on tax evasion. The lower the tax technology and information, it is encouraging to reduce the rate of tax evasion if it has been conveyed properly and taxpayers understand the technology that has been applied. Taxpayers’ knowledge affects tax evasion. The lower the taxpayer’s knowledge, the more it will contribute to reducing tax evasion if taxpayers have information about taxes.